2012
DOI: 10.1007/s00592-012-0390-5
|View full text |Cite
|
Sign up to set email alerts
|

Human pericyte–endothelial cell interactions in co-culture models mimicking the diabetic retinal microvascular environment

Abstract: Background: Pericytes regulate vascular tone, perfusion pressure and endothelial cell (EC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…A C C E P T E D ACCEPTED MANUSCRIPT 60 retinopathy in vitro and in vivo (Beltramo et al, 2009;Berrone et al, 2006;Hammes et al, 2003;Tarallo et al, 2012). A clinical trial tested the ability of benfotiamine to reduce plasma and urinary AGEs but showed no benefit (Alkhalaf et al, 2012) and in T1D patients, 24 month treatment with benfotiamine demonstrated no change in peripheral nerve function or soluble inflammatory biomarkers (Fraser et al, 2012).…”
Section: Therapeutic Options In Diabetic Retinopathymentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 60 retinopathy in vitro and in vivo (Beltramo et al, 2009;Berrone et al, 2006;Hammes et al, 2003;Tarallo et al, 2012). A clinical trial tested the ability of benfotiamine to reduce plasma and urinary AGEs but showed no benefit (Alkhalaf et al, 2012) and in T1D patients, 24 month treatment with benfotiamine demonstrated no change in peripheral nerve function or soluble inflammatory biomarkers (Fraser et al, 2012).…”
Section: Therapeutic Options In Diabetic Retinopathymentioning
confidence: 99%
“…Benfotiamine, a lipid soluble thiamine (vitamin B1), prevents hyperglycemiainduced pericyte-endothelial cell interactions [87]. In diabetic rats, Benfotiamine has been shown to inhibit the development of histopathology characteristic of diabetic retinopathy via inhibiting the major biochemical pathways implicated in its pathogenesis [88].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, insulin treatment cannot fully prevent the development of the severe chronic complications related to diabetes, such as kidney failure, coronary heart disease, retinopathy, and neuropathy [37]. Islet transplantation is a relatively low-invasive procedure that has been shown to normalize glycemia and effectively counteract the development of diabetic complications [813].…”
Section: Introductionmentioning
confidence: 99%